2021
DOI: 10.3390/ani11051243
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Green Algae (Spirulina platensis) Alleviates the Negative Impact of Heat Stress on Broiler Production Performance and Redox Status

Abstract: The modern broiler industry faces huge challenges to keep high production quality and quantity, especially under environmental heat stress conditions. The negative effect of heat stress on broiler productivity is mediated by oxidative stress induction. The blue-green alga (Spirulina platensis) has many applications in poultry nutrition with the high levels of bioactive antioxidant compounds, which can alleviate the oxidative stress damage induced by high ambient temperature. The current study was designed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 64 publications
4
29
1
Order By: Relevance
“…Abdominal fat (%) was not altered in all treated groups. These results agree with Moustafa et al ( 2021 ) and Hajati andZaghari ( 2019 ), who reported that dietary inclusion of S. platensis powder at 0.25, 0.5, and 1% improved carcass traits of broilers reared under hot and thermoneutral conditions. Moreover, Khan et al ( 2020a ) documented that 0.2% of dietary S. platensis increased dressing percentage but did not affect abdominal fat (%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Abdominal fat (%) was not altered in all treated groups. These results agree with Moustafa et al ( 2021 ) and Hajati andZaghari ( 2019 ), who reported that dietary inclusion of S. platensis powder at 0.25, 0.5, and 1% improved carcass traits of broilers reared under hot and thermoneutral conditions. Moreover, Khan et al ( 2020a ) documented that 0.2% of dietary S. platensis increased dressing percentage but did not affect abdominal fat (%).…”
Section: Discussionsupporting
confidence: 91%
“…However, Sugiharto et al ( 2018 ) showed no detrimental effect of Spirulina on hepatic or renal function biomarkers. In contrast, Moustafa et al ( 2021 ) showed that dietary inclusion of Spirulina enhanced liver enzymes activity and renal biomarkers of heat-stressed broilers.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…HS has caused huge economic losses to the livestock industry [ 29 ]. Research shows that HS severely affects animal health and performance [ 30 ]. In our current research, the Final BW, ADFI, and ADG in the HS group were significantly lower than in the CON group, suggesting the harmful effects of HS on chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Among the algae, Spirulina (Arthrospira) platensis contains high protein (55-70%) and amino acid that resembles soybean meal, and may therefore be a viable alternative protein source for chickens (Mullenix et al 2021a,b). In this case, S. platensis has been included in diets as a source of protein and exerted growth promoting effect on broiler chickens (Islam et al 2021;Moustafa et al 2021). Spirulina platensis also contains a variety of functional components such as vitamins, essential fatty acids, minerals, antioxidants and pigments, which are beneficial for the health conditions of chickens (Liestianty et al 2019;Islam et al 2021).…”
Section: Introductionmentioning
confidence: 99%